Highly efficient and low-cost process for synthesis of 2-O-α-d-glucopyranosyl-6-O-(2-propylpentanoyl)-l-ascorbic acid. (December 2021) - Iwaoka, Yuji; Fukushima, Misaki; Ito, Hideyuki; Tai, Akihiro
Graphical abstract: Highlights: An efficient process of 6-bOcta-AA-2G without using pyridine was established. The efficient production process by CGTase with soluble starch and amyloglucoaidase. The yield by this process was about 3-times higher than that by the previous process. This process is superior to the previous process in terms of efficiency and cost. Abstract: 2- O -α-d- Glucopyranosyl-6- O -(2-propylpentanoyl)-l -ascorbic acid (6-bOcta-AA-2G) has shown a remarkable antitumor effect in an in vivo study. However, an efficient and low-cost process for synthesis of 6-bOcta-AA-2G has not been established yet. The process used for synthesis of 6-bOcta-AA-2G in this study consisted of three steps. The first step was acylation of l -ascorbic acid (AA) at the C-6 position with 2-propylpentanoic acid in concentrated H2 SO4 at room temperature for 24 h to obtain 6- O -(2-propylpentanoyl)-l -ascorbic acid (6-bOcta-AA). Next, specific glycosylation of 6-bOcta-AA at the C-2 position by cyclodextrin glucanotransferase (CGTase) from Thermoanaerobacter sp. was carried out using soluble starch as a low-cost glycosyl donor in acetate buffer (pH 6.0) at 40 °C for 24 h. In this glycosylation reaction by CGTase, oligoglucosylated 6-bOcta-AAs seemed to be generated, and thus these oligoglucosides were further hydrolyzed by amyloglucosidase from Rhizopus sp. at 40 °C for 1 h in the reaction mixture containing CGTase to efficiently obtain 6-bOcta-AA-2G. The overall yield of 6-bOcta-AA-2G was 19.4 %. The presented synthetic process can be used for mass production of 6-bOcta-AA-2G as an antitumor agent.